Impact of MGNREGA: A Case Study in an Arid Village of Western Rajasthan - Saha, D K; Srivastava, Soma; Chand, Khem (Annals of Arid Zone, 2016)
The impact of MGNREGA (Mahatma Gandhi National Rural Employment Guarantee Act) was studied on socio-economic and ecological lives of desert dwellers in an arid area of western Rajasthan. Analysis of primary data indicated that overall 12.14% of the total income was derived from MGNREGA. The non-availability of labor for timely agricultural operations was primarily due to increased wage rate. Farmers cope up with the situation through use of family labor, mutual exchange of labor and partly hiring from outside. The movement of daily wage laborer for wage earnings to nearby urban centers was declined by 18%. The women empowerment in real sense may take some more time as the program has started only in 2008. Key words: MGNREGA, impact, women empowerment, socio-economics, poverty alleviation, water harvesting, wage earnings.